Introduction: exponential inequalities: what can equality law do? - Atrey, S; Fredman, S (Oxford University Press, 2023)
The purpose of the introductory chapter is twofold: first, to explain the meaning of the term 'exponential inequalities' which is the subject of this book; and, secondly, to set out the context and significance of the research in the individual contributions and the book as a whole. The chapter shows how the book uses a comparative and interdisciplinary approach to isolate the features of exponential inequalities that have arisen during the pandemic and other past crises, and to lay down a template of thinking about exponential inequalities in future crises such as climate emergencies, democratic deficits, wars, refugee crises, etc. It also explains how equality law in international and comparative contexts has responded to exponential inequalities and identifies the normative and doctrinal gaps that exist in equality law across jurisdictions. Finally, the chapter points to the possibilities within the extant normative and doctrinal framework of equality law to address exponential inequalities.